Studi Geologi Teknik dan Kestabilan Lereng di Ruas Jalan Kendari-Andoolo, Kecamatan Wolasi, Kabupaten Konawe Selatan, Sulawesi Tenggara - Masri; Nurul Fauziah; Syamsul Razak Haraty; Laode Ngkoimani; Harisma (Jurnal Rekayasa Geofisika Indonesia, 2023)
This research presents the engineering geological features of the Kendari-Andoolo road section, Wolasi Sub-district, South Konawe Regency, Southeast Sulawesi, a vulnerable area for landslides. The slope factor of safety (FoS) was also determined using the limit equilibrium method on a single and overall slope. Hand auger drilling and Wenner-Schlumberger configuration geoelectric surveys were conducted to estimate the slope failure plane. The study area is composed of phyllite, mudstone, and sandstone. Discontinuities at the face of the slope are N45ºE and N105ºE shear fractures, N280ºE foliation, and N310ºE fault brecciation. The overburden is low plasticity organic silt (OL) with a density range of 16.92 kN/m3-18.01kN/m3 and a plasticity index of 8.64-10.57 (medium). The FoS values of the slopes assumed rotational and nonrotational slip failures. On a single slope assuming rotational failures, the FoS value was lower than the nonrotational plane but still above the threshold value. The critical FoS is on the rotational sliding plane on the overall slope model. The slope's landslide failure plane is the clay's boundary layers and weathered phyllite.